1989
DOI: 10.1002/ajmg.1320340208
|View full text |Cite
|
Sign up to set email alerts
|

Familial abdominal wall defects

Abstract: We report 2 families, each having multiple sibs with abdominal wall defects. In family 1, normal parents gave birth to identical (monochorionic, diamniotic) twins. This is the first reported case of gastroschisis occurring in monozygotic twins. In family 2, a normal mother gave birth to a son with omphalocele. Two subsequent pregnancies with a different husband resulted in a stillborn girl with partial atresia of the colon and a liveborn girl with gastroschisis. In neither case were there any associated anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Gastroschisis occurrence in a set of monozygotic twins has been reported with a separate report of a pair of siblings, one with gastroschisis and the other with exomphalos (Hershey et al 1989). Data from the Californian Birth Defects Registry (1988Registry ( to 1990 reported that in six (4.7%) out of 127 extended pedigrees of families with a case of gastroschisis more than one relative was affected (Torfs and Curry, 1993).…”
Section: Introduction -Abdominal Wall Defectsmentioning
confidence: 99%
“…Gastroschisis occurrence in a set of monozygotic twins has been reported with a separate report of a pair of siblings, one with gastroschisis and the other with exomphalos (Hershey et al 1989). Data from the Californian Birth Defects Registry (1988Registry ( to 1990 reported that in six (4.7%) out of 127 extended pedigrees of families with a case of gastroschisis more than one relative was affected (Torfs and Curry, 1993).…”
Section: Introduction -Abdominal Wall Defectsmentioning
confidence: 99%
“…b Diagnosed as ruptured omphalocele; only intestine protruded through the defect; no other anomalies have been detected. It seems likely that this boy had a gastroschisis, too [21].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Data on the racial background of affected mothers were given in 13 instances, with 10 of them white [5,21,42,46,47], 1 Hispanic [42], 1 Chinese [44], and 1 of a nonwhite racial background, not otherwise specified [5]. This distribution corresponds with the known preponderance of gastroschisis among white people [52].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations